P443 Haemorrhoidal Artery Ligation – Recto-Anal Repair (HAL-RAR) with mucopexy for grade III hemorrhoids in IBD patients. (27th May 2021) - Laureti, S; Cardelli, S; Gionchetti, P; Rizzello, F; Calabrese, C; Poggioli, G
Abstract: Background: Symptomatic hemorrhoids represent an important and sometimes underestimate chapter of perianal Inflammatory Bowel Diseases (IBD), with an incidence reported up to 20.7%. At present, there is still no consensus in the scientific community on the exact indications of surgery in IBD patients presenting with symptomatic haemorrhoids, due to the reported high risk of postoperative complications. We describe our experience with Haemorrhoidal Artery Ligation – Recto-Anal Repair (HAL-RAR) hemorrhoidopexy in highly selected patients with IBD. Methods: This was a single-center longitudinal study of a cohort of patients with both Ulcerative Colitis (UC) and Crohn's Disease (CD) who underwent HAL-RAR using a dedicated doppler-guided probe (Trilogy™) for symptomatic grade III hemorrhoids not responding to medical therapy. Short and long-term postoperative morbidity were recorded. Severity of hemorrhoid symptoms, specifically bleeding, prolapse, manual reduction, discomfort or pain and impact on quality of life (Giordano score) and fecal continence status (Vaizey score) were evaluated before surgery and at minimum of 6 months after surgery. Results: Sixteen patients with symptomatic grade III haemorrhoids underwent HAL-RAR (12 female). The mean age was 49 yrs old (37–66). Twelve had CD and 4 UC; none presented with anorectal or perianal involvement. All patients were taking optimal medical treatment for IBD. Only the patients with CDAI<150 and Full Mayo score of 1 (with endoscopic sub-score of 0) were included. Mean follow-up was 27.8 months (9–76). The mean operating time was 46 minutes. Short-term complications included one patient requiring prolonged analgesia with NSAIDs for two weeks, one patients needing hospitalization for bleeding after 10 days, treated conservatively and one patient with acute urinary retention, resolved after catheterization. The was no abscess or fistula formation. During the follow-up period, no patients suffered from recurrent haemorrhoidal bleeding and none had recurrent prolapse. A 66 yrs old female reported at 6 months post-operatively the worsening of Vaizey score from 4 to 6 due to the need of taking costipating medicines. All patients report significant amelioration of quality of life. Conclusion: Our results show that HAL-RAR Hemorrhoidopexy is a safe and effective technique for treating grade III symptomatic hemorrhoids in highly selected IBD patients without anorectal involvement. These results need to be validated in large and multicenter trials.